2002
DOI: 10.1002/jnr.10286
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of amyloid β toxicity in Alzheimer's disease model Tg2576 by intraventricular antiamyloid β antibody

Abstract: There are considerable data on synaptic dysfunction in Alzheimer's disease (AD). However, the precise molecular basis for synaptotoxicity in AD is not known. We tested the hypothesis that amyloid beta (Abeta), as produced in Tg2576 mice overexpressing a mutant form of amyloid precursor protein, leads to changes in SNAP-25, a molecule required for Ca-sensitive neurotransmitter vesicle exocytosis. Anti-Abeta antibody was injected into the third ventricle (icv) of 10-month-old Tg2576 mice, preceding formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 83 publications
4
47
0
Order By: Relevance
“…Interestingly, alterations in the distribution of mossy fibers are related to long-term plasticity (Cremer et al, 1998) and long-term memory (Ramirez-Amaya et al, 2001). Consistent with our data, SNAP-25 (synaptosomal associated protein 25), a protein involved in vesicle exocytosis, was also strikingly reduced in the stratum lucidum of Tg2576, confirming a presynaptic loss in this model (Chauhan and Siegel, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, alterations in the distribution of mossy fibers are related to long-term plasticity (Cremer et al, 1998) and long-term memory (Ramirez-Amaya et al, 2001). Consistent with our data, SNAP-25 (synaptosomal associated protein 25), a protein involved in vesicle exocytosis, was also strikingly reduced in the stratum lucidum of Tg2576, confirming a presynaptic loss in this model (Chauhan and Siegel, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…By using electron microscopy, these authors also reported that Aβ-treated neurons displayed reduced number of synaptic vesicles, especially those near the presynaptic active zones and a reduction in several presynaptic proteins (Parodi et al, 2010). Accordingly, presynaptic proteins such as SNAP-25, synaptophysin, and synaptotagmin were reduced in brains of patients with AD (Reddy et al, 2005) and in the hippocampus of Tg2576 mice 1 month after injection of Aβ into the third ventricle (Chauhan and Siegel, 2002 (Russell et al, 2012). Additionally, Aβ oligomers can alter dynamin-1, a neuron-specific GTPase that pinches off synaptic vesicles, allowing them to re-enter the synaptic vesicle pool (Kelly et al, 2005;Kelly and Ferreira, 2006).…”
Section: Aβ At Presynaptic Level and Glial Cellsmentioning
confidence: 88%
“…Other studies, however, did not show effects of A␤ on NMDA neurotransmission, indicating some complexities (9). On the other hand, presynaptic proteins such as SNAP-25, synaptophysin, and synaptotagmin have also been reported to be reduced in brains of patients with AD and after treatment with A␤ (10,11). Additionally, A␤ oligomers can alter dynamin-1, a neuron-specific mechanochemical GTPase that pinches off synaptic vesicles, allowing them to reenter the synaptic vesicle pool (12,13).…”
mentioning
confidence: 98%